Spiritualitas Kepemimpinan Hamba Menurut Bonhoeffer dan Relevansinya Bagi Pelayanan Pendeta - Winanda Nebuida (EULOGIA: Jurnal Teologi dan Pendidikan Kristiani, 2026)
This study explores the relevance of Dietrich Bonhoeffer's theological ethics, particularly his concepts of "Christ existing as community," critique of power abuse, and "serving from below," for pastoral leadership in Indonesia. Using a qualitative method with literature study, this research analyzes Bonhoeffer's works and their application to the challenges of power dynamics, pluralism, and digitalization in Indonesian churches. The findings indicate that Bonhoeffer's ethics offer a critical framework for transforming pastoral leadership from hierarchical models to servant-oriented, community-based ministry. This approach strengthens church integrity and contextual relevance in facing contemporary social and digital challenges. The study concludes that integrating Bonhoeffer's thought can prevent power abuse and promote humble, inclusive leadership within Indonesia's multicultural context.